Impact of MWCNT concentration on the piezo-impedance response of porous MWCNT/PDMS composites - Lim, Seok Ju; Lim, Hyun Su; Joo, Yongho; Jeon, Dae-Young (ELSEVIER SCIENCE SA, 2020)
Carbon nanotube (CNT) based physical sensors with high performance have been successfully applied to novel devices for human motion detection and healthcare monitoring. Here, porous multi-walled car-bon nanotube/polydimethylsiloxane MWCNT/PDMS composites with different MWCNT contents were fabricated via the water-oil emulsion state, and their impedance characteristics were investigated in detail. Intermediate MWCNT content induced both resistive and capacitive properties in the composites, while the composite with the highest MWCNT concentration showed resistive-dominant properties. In addition, an excellent piezo-impedance physical sensor using the MWCNT-loaded composites was demonstrated using an improved impedance sensing method. This work provides key information for realizing practical applications of MWCNT/PDMS composites. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: INTERDIGITATED ELECTRODE ARRAYS; STRAIN; SENSORS; FILMS